Implementation of Integration VaaMSN and SEMAR for Wide Coverage Air Quality Monitoring - Yohanes Yohanie Fridelin Panduman; Adnan Rachmat Anom Besari; Sritrusta Sukaridhoto; Rizqi Putri Nourma Budiarti; Rahardhita Widyatra Sudibyo; Funabiki Nobuo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The current air quality monitoring system cannot cover a large area, not real-time and has not implemented big data analysis technology with high accuracy. The purpose of an integration Mobile Sensor Network and Internet of Things system is to build air quality monitoring system that able to monitor in wide coverage. This system consists of Vehicle as a Mobile Sensors Network (VaaMSN) as edge computing and Smart Environment Monitoring and Analytic in Real-time (SEMAR) cloud computing. VaaMSN is a package of air quality sensor, GPS, 4G WiFi modem and single board computing. SEMAR cloud computing has a time-series database for real-time visualization, Big Data environment and analytics use the Support Vector Machines (SVM) and Decision Tree (DT) algorithm. The output from the system are maps, table, and graph visualization. The evaluation obtained from the experimental results shows that the accuracy of both algorithms reaches more than 90%. However, Mean Square Error (MSE) value of SVM algorithm about 0.03076293, but DT algorithm has 10x smaller MSE value than SVM algorithm.